Experimental gas jet studies for the IGISOL LIST method and simulation modeling - Pohjalainen, Ilkka (2010)
The IGISOL Laser Ion Source Trap (LIST) is a method in which a supersonic gas jet is used to transport thermalized nuclear reaction products from a gas cell into a sextupole radio frequency ion guide (SPIG) while removing any non-neutral part of the jet by a positively biased repeller electrode. Specific atom species are resonantly re-ionized with laser radiation in the SPIG which enables the study of exotic nuclei without isobaric contamination. In the first part of this work the repelling effect is studied through a series of ion optical Monte-Carlo simulations. The simulations were able to support the hypothesis that the constant collisions between the fast moving buffer gas atoms and the ions provides additional momentum to overcome potential barriers of several tens of volts, explaining the need for high repelling electrode potentials in practice. The simulations were also used to investigate the differences between helium and argon buffer gases and different repelling geometries. The experimental behaviour of the repelling efficiency as a function of repelling potential was qualitatively reproduced. The second part of this work concentrated on the supersonic gas jet formation and the parameters that affect the gas jet properties, in particular the width. For an efficient transportation of atoms from the gas cell to the SPIG the gas jet needs to be well collimated. The gas jet behaviour was investigated with two nozzle shapes and diameters in varying pressure environments by photographing plasma afterglow in the gas expanding from an arc discharge ion guide. It was found that the jet width is strongly dependent on background pressure and independent of the nozzle shape and gas cell pressure. Because the gas jet exhibited a collimated behaviour only with increasing background pressure, a new de Laval type of nozzle was introduced. This nozzle produced a narrow collimated jet structure at background pressures as low as 0.33 mbar.